Atrial fibrillation is associated with central sleep apnea in clinic patients undergoing diagnostic polysomnography. Issue 6 (3rd September 2020) - Harmon, Evan Kenneth; Stafford, Patrick; Ibrahim, Sami; Cho, Yeilim; Mazimba, Sula; Bilchick, Kenneth; Lin, Gen‐Min; Park, Seung‐Jung; Aliasghar Gharib, Sina; Kapur, Vishesh K.; Kwon, Younghoon
Abstract: Introduction: Sleep apnea is highly prevalent in patients with atrial fibrillation (AF). Obstructive sleep apnea (OSA) is the most common type, and best studied in the context of AF. However, recent investigations have indicated that central sleep apnea (CSA) may be a risk factor for incident AF. We evaluated the burden of CSA events in patients referred for diagnostic polysomnography (PSG) and whether AF is associated with CSA. Methods: We identified patients with and without a history of AF who underwent clinically indicated PSG in a matched manner. OSA was defined as obstructive apnea‐hypopnea index (AHI) ≥15/h, and CSA was defined as central apnea index (CAI) ≥5/h. The association between AF and CSA was evaluated using multivariable logistic regression. Results: Among 465 patients included, mean AHI was 25.5/h, and mean CAI was 1.7/h. OSA prevalence was 53.3%, while CSA prevalence was 8.4%. The prevalence of OSA in the AF and non‐AF groups (54.7% vs 52.0%, P  = .56) was similar. CSA was more common in the AF group (12.3% vs 4.4%, P  = .002). In multivariable analysis, AF (OR: 2.19 [1.02, 5.03], P  = .05), male gender (OR: 2.5 [1.17, 5.84], P  = .02), and older age (OR: 2.44, [1.16, 5.46], P  = .02) were associated with CSA. Conclusion: Though CSA is much less common than OSA in patients with AF, the presence of AF is independently associated with CSA. Abstract : In this study, we analyzed the central sleep apnea burden of patients with and without atrial fibrillation undergoing diagnostic polysomnography. We found that central sleep apnea, though uncommon, was independently associated with atrial fibrillation.